2000
DOI: 10.1177/000348940010900801
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Functional Study of Regenerated Chorda Tympani Nerves in Humans

Abstract: It is still unclear whether the chorda tympani nerves in humans regenerate after being severed during middle ear surgery, although functional studies have demonstrated recovery of taste 1 to 2 years after surgery. To date, 12 cases of regenerated chorda tympani nerves have been found in our series of patients during secondary surgery. The regenerated nerves of 3 cases of the 12 were removed as samples during secondary surgery to detect regenerated myelinated axons. All regenerated nerves were in the submucosal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Some previous clinical studies have reported that patients feel abnormal pain sensation after wound healing [18-20]. When considering the previous data and our findings, it is possible that an abnormal pain sensation occurs in the cutaneous tissues reinnervated by the injured nerves, but how the reinnervated nerves are involved in generation of an abnormal pain in the areas innervated by the injured IAN is not well understood.…”
Section: Discussionsupporting
confidence: 42%
“…Some previous clinical studies have reported that patients feel abnormal pain sensation after wound healing [18-20]. When considering the previous data and our findings, it is possible that an abnormal pain sensation occurs in the cutaneous tissues reinnervated by the injured nerves, but how the reinnervated nerves are involved in generation of an abnormal pain in the areas innervated by the injured IAN is not well understood.…”
Section: Discussionsupporting
confidence: 42%
“…Therefore, it is possible that injury-induced plasticity of nerve terminal fields is complex, involving multiple gustatory nerve terminal fields. Such changes may underlie the apparent compensation needed to protect normal taste-elicited behaviors following nerve damage and may be induced in humans through taste nerve damage sustained as a result of disease (Arnold, 1974; Bull, 1965; May and Schlaepfer, 1975), middle ear surgery (Saito et al, 2000, 2001a,b, 2002), or oral surgery (Gent et al, 2003; Schendel and Epker, 1980). …”
Section: Discussionmentioning
confidence: 99%
“…In surgical patients the TB recover once the CT nerve regenerates after surgery [93,104], followed by recovery of taste sensation [105,106,107]. Neurotrophins, particularly BDNF, have been reported to mediate the nerve regeneration after CT section in mice [57,58].…”
Section: Chemosensation Somatosensation Hh Signaling and Disrupmentioning
confidence: 99%